2021
DOI: 10.1111/sms.14098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balance training with stroboscopic glasses on postural control in chronic ankle instability patients

Abstract: Individuals with chronic ankle instability (CAI) are believed to rely more on visual information during postural control due to impaired proprioceptive function, which may increase the risk of injury when their vision is limited during sports activities. Objectives: To compare (1) the effects of balance training with and without stroboscopic glasses on postural control and (2) the effects of the training on visual reliance in patients with CAI. Design: A randomized controlled clinical trial. Methods: Twenty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the present study, the COP 95% confidence ellipse area was measured during drop landing and it was confirmed that both PEG and SEG significantly decreased the ellipse area compared to NTG. In a study by Lee et al [44], patients with CAI were asked to perform dynamic lower extremity balance exercises for 4 weeks, and significant differences were found in both the anterior/posterior, left/right velocity, and movement range of the COP. This means that 4 weeks of balance exercise led to an increase in proprioceptor and joint receptor thresholds, sensory function, ankle stability and dynamic postural control function in patients with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the COP 95% confidence ellipse area was measured during drop landing and it was confirmed that both PEG and SEG significantly decreased the ellipse area compared to NTG. In a study by Lee et al [44], patients with CAI were asked to perform dynamic lower extremity balance exercises for 4 weeks, and significant differences were found in both the anterior/posterior, left/right velocity, and movement range of the COP. This means that 4 weeks of balance exercise led to an increase in proprioceptor and joint receptor thresholds, sensory function, ankle stability and dynamic postural control function in patients with CAI.…”
Section: Discussionmentioning
confidence: 99%
“…This inaccurate perception may lead to compensatory responses that are inappropriate to correct for the loss of stability ( Anson and Jeka, 2010 ), because somatosensation is the most important system for postural control, as it provides the fastest information processing ( Campbell, 2007 ). Against this background, optic flow perturbations might be a helpful tool that should be considered when developing rehabilitation programs, as they could help patients to decrease reliance on visual information during balance control and upregulate reliance on somatosensory information for motor programming ( Lee et al, 2021 ; Han et al, 2022 ). The implementation of this novel approach may enhance the activity of the somatosensory pathways to the postural system due to limited visual information input ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hip strategy undertakes most of the buffering load tasks. Studies of postural strategies related to the loss of proprioception and vestibular function have found that the hip strategy is adopted more when joint instability occurs ( Horak et al, 1990 ; Lee and Bo, 2021 ; Lee et al, 2022 ). Furthermore, the body mainly relies on the ankle strategy to adjust postural stability when interferences are few or when environmental information changes, but the hip strategy also dominates for large changes.…”
Section: Practical Implicationsmentioning
confidence: 99%